Tarannum Interactive Audio Book Model: Towards a Harmonious Assimilation of Information and Communication Technology into Quranic Education - Mohd Zaini Zakaria; Hapini Awang; Mohd Nur Adzam Rasdi; Ramlan Mustapha (Uitm Pahang, 2024)
Volume 1, Issue 2 (page: 37-45)